Identifying phage Lysins through genomic analysis of prophages from Acinetobacter baumannii - Raposo, Maria Leonor; Pimentel, Ana Carolina; Manageiro, Vera; Duarte, Aida; Caniça, Manuela; Vale, Filipa F. (Frontiers in Microbiology, 2025)
Acinetobacter baumannii is a Gram-negative opportunistic pathogen, responsible for nosocomial infections worldwide. In recent years, this microorganism has acquired resistance to various antibiotics, prompting the World Health Organization (WHO) to declare carbapenem-resistant A. baumannii (CRAB) a critical priority microorganism requiring urgent attention and the development of new therapeutic options. Here, we screened for prophages in 158 genomes of A. baumannii, comprising 139 complete genomes from the Bacterial and Viral Bioinformatics Resource Center (BV-BRC), and 19 newly sequenced clinical isolates. Additionally, we conducted phylogenetic analyses of prophages, highlighting their diversity and local clustering. The analyzed genomes harbored at least two prophage regions, resulting in the identification of a total of 950 prophage regions, of which 348 were considered complete prophages through software analysis and manual curation, while the remainder may represent prophage remnants. The complete prophages ranged from 28.6 to 103.9 kbp, with an average GC content of 39%. Based on genomic similarity, only 18 complete prophages were taxonomically classified to the genus Vieuvirus. Among all identified complete prophages, we identified 166 genes encoding for putative lysins, while prophage regions that were not considered complete could also harbor putative lysins. These findings highlight the abundance of prophage-encoded lysins in A. baumannii genomes, which are promising therapeutic agents for combating A. baumannii infections, particularly in the face of rising antibiotic resistance.